Aplikasi Maps Interaktif Kampus I Dan Kampus Ii Universitas Muhammadiyah Surakarta Pada Perangkat Android - Prasetya, Joko, Heru Supriyono,. S.T,. M.T,. Ph.D (2016)
Muhammadiyah university or known as UMS is one of private universities in Indonesia. UMS has only floor plan layout of building in offline form however. Acording to the background of issue, the writer wants to make the blueprint of UMS in online form by using smartphone android. In making UMS interactive map application based on android, the writer use java script as the the language programme and eclipse software to make a design of application system with the once which has been installed with ADT. When the system is done, then is must be examined with SDK or directly using smartphone. While in designing the picture and icon are using potoshop and inkcape software. Maps interactive application of UMS can show building and the major that accupy the building. The information that given is also including the building picture and information abaut the major in UMS.